The structure of the crowd and its psychological behavior in the Maqamat of Badi' al-Zaman al-Hamadhani (Al-Farooq Journal of Sciences, 2026)
This research endeavors to explore the phenomenon of the crowd in selected Maqamat of Badi' al-Zaman al-Hamadhani, treating it as an active entity, in order to deconstruct its structural formation and analyze its psychological dynamics. The significance of this study lies in offering an interdisciplinary approach that liberates the text from the confines of purely rhetorical readings, repositioning it as a profound socio-psychological document. The research is structured into a prelude and two main sections: the first examines the structural formation of crowds (ritualistic, emotional, and random), while the second traces the gradual stages of their behavior, from the dissolution of individuality and the contagion of influence, to the ultimate awakening. The study concludes by affirming Al-Hamadhani’s pioneering insight in observing the nature of the masses, asserting that the crowd is an active narrative agent governed by the laws of suggestion, which inevitably culminates in its disintegration and the discovery of the deception.
Keywords: Collective Consciousness - Suggestion - Emotional Contagion - Mendicancy - Narrative Space